Phosphodiesterases Regulate BAY 41-2272-Induced VASP Phosphorylation in Vascular Smooth Muscle Cells - Adderley, Shaquria P.; Joshi, Chintamani N.; Martin, Danielle N.; Tulis, David A. (Frontiers in Pharmacology, 2012)
BAY 41-2272 (BAY), a stimulator of soluble guanylyl cyclase, increases cyclic nucleotides and inhibits proliferation of vascular smooth muscle cells (VSMCs). In this study, we elucidated mechanisms of action of BAY in its regulation of vasodilator-stimulated phosphoprotein (VASP) with an emphasis on VSMC phosphodiesterases (PDEs). BAY alone increased phosphorylation of VASPSer239 and VASPSer157, respective indicators of PKG and PKA signaling. IBMX, a non-selective inhibitor of PDEs, had no effect on BAY-induced phosphorylation at VASPSer239 but inhibited phosphorylation at VASPSer157. Selective inhibitors of PDE3 or PDE4 attenuated BAY-mediated increases at VASPSer239 and VASPSer157, whereas PDE5 inhibition potentiated BAY-mediated increases only at VASPSer157. In comparison, 8Br-cGMP increased phosphorylation at VASPSer239 and VASPSer157 which were not affected by selective PDE inhibitors. In the presence of 8Br-cAMP, inhibition of either PDE4 or PDE5 decreased VASPSer239 phosphorylation and inhibition of PDE3 increased phosphorylation at VASPSer239, while inhibition of PDE3 or PDE4 increased and PDE5 inhibition had no effect on VASPSer157 phosphorylation. These findings demonstrate that BAY operates via cAMP and cGMP along with regulation by PDEs to phosphorylate VASP in VSMCs and that the mechanism of action of BAY in VSMCs is different from that of direct cyclic nucleotide analogs with respect to VASP phosphorylation and the involvement of PDEs. Given a role for VASP as a critical cytoskeletal protein, these findings provide evidence for BAY as a regulator of VSMC growth and a potential therapeutic agent against vasculoproliferative disorders.